Factors influencing oral expression among Arabic language students of Nigerian Colleges of Education - Muhammad Usman; Hassan, Abd Rauf; Abdul Jabar, Mohd Azidan (University of Jordan,Deanship of Scientific Research, 2022)
The study aims at identifying factors responsible for poor oral expression among students of Arabic language from the teachers’ perspectives in Colleges of Education in Abuja and Niger State, Nigeria. The study adopted quantitative method for data collection and analysis, hence, a questionnaire which consists of (26) items distributed in five sections was developed to achieve the research objectives. The results revealed that the teachers’ grading of the factors responsible for the poor oral expression was very high, and the factors related to the learner’s attitude towards study got the teachers’ highest grading (M=4.60), while the factors related to syllabus earned teachers’ lowest grades (M=3.83). The results also revealed that there were no statistically significant differences at the significance level (α=0.05) for the same factors according to teaching experience.